The poisoning mechanism of N2O reductive catalysts and anti-interference modification/regeneration technology - Wu Pengfei; Guan Bin; Zhu Lei; Zhu Tiankui; Chang Shiying; Ma Jiangli; Wang Rong; Yang Dongxia; Shu Kaiyou; Zhuang Zhongqi; Chen Junyan; Gao Junjie; et al. (Journal of Environmental Chemical Engineering, 2026)

Natural organic matter concentration controls the coordination and redox interaction between cerium ions and manganese oxides - Aling Wan; Bei Liu; Meng Zhang; Weiwen Chen; Iso Christl; Mengxia Wang; Xinyu Rong; Yufei Shu; Zhongying Wang (Journal of Hazardous Materials, 2026)

Botany, extraction methods, chemical constituents, pharmacological activities, and food applications of Stauntonia chinensis - Chen-Yu Chang; Xiao-Yun Wang; Ke-Jia Liu; Qi Li; Shu-Yan Lu; Qin-Ge Ma; Rong-Rui Wei (Natural Product Research, 2026)

Longitudinal multi-omics unveils rice-fish co-culture promotes common carp health and growth via microbiome remodeling - Chang Fang; Shi-jun Chen; Ke-ni Chen; Nian-nian Zhang; Bing Fu; Shu-ping Zhang; Si-yuan Xiong; Jia-en Zhang; Hui-rong Yang (Aquaculture, 2026)

Copper recovery from the smelting products of copper electroplating sludge by roasting and slurry electrolysis - Jinchuan Qin; Rong Wang; Yin Huang; Qian Liang; Jiancheng Shu; Mengjun Chen (Waste Management, 2026)

A novel phytoformula targeting lipid peroxidation inhibition attenuates UV-induced skin photoaging - Ling-Ping Wu; Wei Chen; Qian-Pei Lin; Shi-Yun Feng; Jin Dai; Qiong-Yi Zhang; Wen-Yi Chen; Hiroshi Kurihara; Xiao-Min Li; Shu-Hua Ouyang; Yi-Fang Li; Rong-Rong He (PharmaNutrition, 2026)

Bioaerosol emission in public washroom under different time intervals of working day and critical exposure time for sanitary workers - Wajid Ali; Zi-qi Yang; Chun-shu Tian; Rui-wen Li; Xu Zhang; Qing Yan; Ke-yu Chen; Si-bo Cheng; Rong-xin Wang; Cheng Yan (Building and Environment, 2026)

Germ layer specification and organotropism in lymphoma invasion - Yan Dong; Peng-Peng Xu; Xiao Han; Yu-Qing Wang; Yi Chen; Ying Fang; Yue Zhu; Qing Shi; Rong Shen; Zi-Yang Shi; Niu Qiao; Shu Cheng; et al. (Science Bulletin, 2026)

GRU-based de novo design and in-silico prioritization of EZH2 inhibitors - Na Yu; Maoqi Wang; Xiaodie Chen; Rong Liu; Liang Zou; Mao Shu (Molecular Diversity, 2026)

A fast powerful X-ray transient from possible tidal disruption of a white dwarf - Dongyue Li; Wenda Zhang; Jun Yang; Jin-Hong Chen; Weimin Yuan; Huaqing Cheng; Fan Xu; Xinwen Shu; Rong-Feng Shen; Ning Jiang; Jiazheng Zhu; Chang Zhou; et al. (Science Bulletin, 2026)

Unique ecological functions of viral communities potentially influence microbial adaptability in deep-sea ferromanganese nodule deposits - Yu-Kang Li; Ge-Yi Fu; Zhen Rong; Jun-Qing Chen; Zhi-Hao Ding; Zu-Xin Zhang; Hua-Hua Jian; Wen-Sheng Shu; Yue-Hong Wu; Xue-Wei Xu (Journal of Hazardous Materials, 2026)

Quantification and geological implications of manganese, barium, and copper observed by MarSCoDe LIBS at Zhurong landing site on Mars - Yuxuan Luo; Zhaopeng Chen; Jianjun Liu; Yizhong Zhang; Jingjing Zhang; Zhibin Li; Xin Ren; Xiangfeng Liu; Zhenqiang Zhang; Weiming Xu; Guolin Hu; Shaojin Han; et al. (Icarus, 2026)

Anti-cancer effects of Psoralea corylifolia: insights into cancer hallmarks - Pin-Rong Chen; Tz-Syuan Su; Kun-Che Chang; Chien-Chih Chiu; Shu-Pin Huang; Hsin-Chih Yeh; Shu-Chi Wang; Chia-Yang Li (Phytochemistry Reviews, 2026)

Hydrothermal acid leaching process with ultra-high efficiency for vanadium from spent catalyst - Quanxian Hua; Junyang Ma; Pin Xu; Shu Zhang; Jingjing Rong; Zehao Chen (Minerals Engineering, 2025)

Fluvial response to differential activity of the Litang fault system: Implications for fault kinematics and geodynamics in the southeastern Tibetan Plateau - Jinhan Wang; Xuhua Shi; Rong Yang; Hanlin Chen; Huili Yang; Yuanhai Shu; Zhuona Bai; Chenchao Xu; Xin Liu (Geomorphology, 2025)

Golgi-associated TRAF6 as a regulator of protein convertase FURIN for insulin receptor precursor processing - Minjun Liu; Kun Zhou; Yang Sheng; Wen Zhang; Qiaoli Chen; Ziyue Chen; Xinyu Yang; Yuxin Jin; Fangtong Liu; Yinqiu Mu; Shu Su; Weikuan Feng; et al. (Science China Life Sciences, 2025)

New aromatic butenolides from the plant endophytic fungus Malbranchea umbrina D16 - Xian-An Chen; Han-Zhuang Weng; Lei-Ming Wu; Shu-Qi Wu; Rong Pu; Tao Yuan; Sheng Yin; Gui-Hua Tang (Natural Product Research, 2025)

Discovery and profiling of efficient microbial strains for struvite biomineralization in high-salinity wastewater - Bing-bing Liu; Rong-ji Zhao; Nimaichand Salam; Shu-hong Xu; Rong Shi; Jiang-hao Zhu; Zi-qing Chen; Cheng-yin Liu; Bing Li; Wen-Jun Li (Antonie van Leeuwenhoek, 2025)

Why is the combined treatment of copper and aluminum more toxic to citrus than single factor treatment? - Wen-Shu Chen; Ti Wu; Tian-Tian Xia; Liang-Yuan Tong; Fei Lu; Xin Ye; Jiuxin Guo; Zeng-Rong Huang; Lin-Tong Yang; Li-Song Chen (Journal of Hazardous Materials, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

The antibacterial activity, action mechanisms and prospects of Baicalein as an antibacterial adjuvant - Liuqing Mu; Kaiyan Xie; Rong Chen; Jiang Cao; Yang Shu; Xuebin Huang (World Journal of Microbiology and Biotechnology, 2025)

Discovery of novel potential 11β-HSD1 inhibitors through combining deep learning, molecular modeling, and bio-evaluation - Xiaodie Chen; Liang Zou; Lu Zhang; Jiali Li; Rong Liu; Yueyue He; Mao Shu; Kuilong Huang (Molecular Diversity, 2025)

Full realization of the RIBLL2 separator at the HIRFL-CSR facility - Xiao-Dong Xu; Yong Zheng; Zhi-Yu Sun; Yu-Nan Song; Bao-Hua Sun; Satoru Terashima; Chang-Jian Wang; Ge Guo; Guang-Shuai Li; Xiu-Lin Wei; Jun-Yao Xu; Ji-Chao Zhang; et al. (Science Bulletin, 2025)

Terpenoids with Antiangiogenic Activity from Formosan Soft Coral Caementabunda hypotentaculata - Hsin Huang; Chen-Yu Yang; Shih-Wei Wang; Limbadri Salendra; Shu-Rong Chen; Tzi-Yi Ke; Yu-Liang Yang; Yu-Chi Lin; Yuan-Bin Cheng (Marine Biotechnology, 2025)

Jarosite residues recycling by slurry electrolysis: Iron recovery and detoxification in one step - Rong Wang; Mengjun Chen; Wei Fan; Xiangfei Zeng; Yunhui Han; Qian Liang; Rong Huang; Songshan Zhou; Jiancheng Shu (Process Safety and Environmental Protection, 2025)

Advances on jarosite residue detoxification and reutilization: a review - Mengjun Chen; Rong Wang; Wei Fan; Jiqin Wang; Xiangfei Zeng; Yunhui Han; Qian Liang; Rong Huang; Songshan Zhou; Jiancheng Shu (Environmental Science and Pollution Research, 2025)

Relationship Between Whole Blood Iron Levels and Lipid Profile Parameters in the General Population: Findings from Routine Physical Examination Report - Rou-Jun Pan; Zhi Luo; Yu-Shun You; Jun-Dong Wang; Ya-Qi Chen; Rong-Rong Zhou; Shu-Zi-Qi Chen; Lin-Min Wang; Jun-Xiang Zhao; Hua-Qin Su; Cai-Li Wang; Li-Fen Zhang; et al. (Biological Trace Element Research, 2024)

Lithium isotopes track changes in continental weathering regimes across the end-Permian mass extinction in Southwest China - Rong-Hui Ye; Feifei Zhang; Guang-Yi Wei; Jianbo Chen; Zhuo Feng; Shu-zhong Shen (Earth and Planetary Science Letters, 2024)

The different impacts of functional network centrality and connectivity on the complexity of brain signals in healthy control and first-episode drug-naïve patients with major depressive disorder - Shanling Ji; Wei An; Jing Zhang; Cong Zhou; Chao-Gan Yan; Xiao Chen; Li-Ping Cao; Wei Chen; Yu-Qi Cheng; Yi-Ru Fang; Qi-Yong Gong; Wen-Bin Guo; et al. (Brain Imaging and Behavior, 2024)

High-resolution ocean color reconstruction and analysis focusing on Kd490 via machine learning model integration of MODIS and Sentinel-2 (MSI) - Yulin Yang; Ziyao Wang; Peng Chen; Xue Shen; Wei Kong; Genghua Huang; Rong Shu (Frontiers in Marine Science, 2024)
Oceanic water quality monitoring is essential for environmental protection, resource management, and ecosystem vitality. Optical remote sensing from space plays a pivotal role in global surveillance of oceanic water quality. However, the spatial resolution of current ocean color data products falls short of scrutinizing intricate small-scale marine features. This study introduces a hybrid model that fuses MODIS (Moderate Resolution lmaging Spectroradiometer) ocean color products with Sentinel-2 ‘s remote sensing reflectance data to generate high-resolution ocean color imagery, specifically investigating the diffuse attenuation coefficient at a wavelength of 490 nm (Kd490). To address the intricacies of coastal environments, we propose two complementary strategies to improve the accuracy of inversion. The first strategy leverages MODIS ocean color products alongside a geographic segmentation model to perform distinct inversions for separate marine zones, enhancing spatial resolution and specificity in coastal regions. The second strategy bolsters model interpretability during training by integrating predictions from conventional physical models into a Random Forest-based Regression Ensemble (RFRE) model. This study focuses on the coastal regions surrounding the Beibu Gulf, near Hainan Island in China. Our findings exhibit a strong concordance with MODIS products, achieving a monthly average coefficient of determination (R²) of 0.90, peaking at 0.97, and sustaining a monthly average root-mean-square error (RMSE) of less than 0.02. These results substantiate the model’s efficacy. Moreover, the annual trend analysis and localized assessment of the reconstructed Kd490 offer nuanced insights that surpass MODIS data, establishing a robust foundation for high-resolution water quality monitoring in coastal zones.

Isobavachin induces autophagy-mediated cytotoxicity in AML12 cells via AMPK and PI3K/Akt/mTOR pathways - Ning Xia; Qing-Hai Chen; Zhao-Jun Meng; Shu-Yue Ma; Jia-Li Huang; Rong Shen; Yu-Tong Dong; Hai-Wei Du; Kun Zhou (Toxicology in Vitro, 2024)

Protective effects of nordalbergin against LPS-induced endotoxemia through inhibiting MAPK/NF-κB signaling pathway, NLRP3 inflammasome activation, and ROS production - Pin-Rong Chen; Chia-Yang Li; Taha Yazal; I-Chen Chen; Po-Len Liu; Yi-Ting Chen; Ching-Chih Liu; Jung Lo; Tzu-Chieh Lin; Ching-Tang Chang; Hsin-En Wu; Yuan-Ru Chen; et al. (Inflammation Research, 2024)

Application of luminescent Photobacterium Phosphoreum T3 for the detection of zearalenone and estimating the efficiency of their enzymatic degradation - Shu-Rong Chen; Li-Hong Chen; Li Pan; Bin Wang (Food Additives & Contaminants: Part A, 2024)

Combination of chemical modifications improves rice protein solubility - Yi-Rong Yang; Wen-Kai Wu; Jhih-Ting Hsiao; Shu-Chen Hsieh; Fuu Sheu (Journal of Cereal Science, 2024)

Genome-wide analysis of in vivo-evolved Candida auris reveals multidrug-resistance mechanisms - Xin-Fei Chen; Han Zhang; Ling-Li Liu; Li-Na Guo; Wen-Jing Liu; Ya-Li Liu; Ding-Ding Li; Ying Zhao; Ren-Yuan Zhu; Yi Li; Rong-Chen Dai; Shu-Ying Yu; et al. (Mycopathologia, 2024)

Differentiation of bone marrow mesenchymal stem cells into Leydig-like cells with testicular extract liquid in vitro - Rong Hua; Fang-Fang Liang; Fang-Qiang Gong; Hua Huang; Yi-Chen Xu; Min He; Yan-Hua Fang; Ya-Shu Wei; Wei-Wei Zhou; Arshad Mehmood; Yi Mo; Zhong Lin (In Vitro Cellular & Developmental Biology - Animal, 2024)

Comparative assessment of leaf photosynthetic capacity datasets for estimating terrestrial gross primary productivity - Mingzhu Xu; Jing M. Chen; Yihong Liu; Rong Wang; Rong Shang; Jiye Leng; Lei Shu; Jane Liu; Ronggao Liu; Yang Liu; Rongjuan Yang; Yulin Yan (Science of The Total Environment, 2024)

A novel method for efficiently recycling platinum group metals and copper by Co-smelting spent automobile catalysts with waste-printed circuit boards - Rong Huang; Songshan Zhou; Jiaming Chen; Xiangfei Zeng; Yunhui Han; Jinchuan Qin; Yao Huang; Fan Lin; Xi Yu; Shushu Liao; Zhiqiang Chen; Yubin Han; et al. (Journal of Cleaner Production, 2024)

Pelagibacterium flavum sp. nov., Isolated from Soil Sample - Xue-Mei Chen; Zu-Zhen Yang; Si-Rong He; Lian-Shuang Xiong; Qing Yuan; Shu-Ya Zuo; Cheng-Lin Jiang; Yi Jiang (Current Microbiology, 2024)

Lack of the CCT domain changes the ability of mango MiCOL14A to resist salt and drought stress in Arabidopsis - Shu-Quan Chen; Cong Luo; Yuan Liu; Rong-Zhen Liang; Xing Huang; Ting-Ting Lu; Yi-Hang Guo; Ruo-Yan Li; Chu-Ting Huang; Zhuo Wang; Xin-Hua He (Plant Science, 2023)

Regulation on copper-tolerance in Citrus sinensis seedlings by boron addition: Insights from root exudates, related metabolism, and gene expression - Huan-Huan Chen; Zhi-Chao Zheng; Wen-Shu Chen; Rong-Yu Rao; Xu-Feng Chen; Xin Ye; Jiuxin Guo; Lin-Tong Yang; Li-Song Chen (Journal of Hazardous Materials, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Inconsistent mercury records from terrestrial upland to coastal lowland across the Permian-Triassic transition - Jianbo Chen; Guangyi Sun; Binjian Lu; Rong-yao Ma; Zhuang Xiao; Yao-feng Cai; Hua Zhang; Shu-zhong Shen; Feifei Zhang; Zhuo Feng (Earth and Planetary Science Letters, 2023)

Zinc efficiently extracted from zinc calcine by reduced wet grinding: ZnFe2O4 to ZnO and Fe3O4 - Shaoqin Chen; Xiangfei Zeng; Qian Liang; Ling Hu; Shuyuan Chen; Dejun He; Yunhui Han; Zhisheng Zhao; Rong Huang; Yin Huang; Songshan Zhou; Jiqin Wang; et al. (Journal of Cleaner Production, 2023)

The mutual interactions among ozone, fine particulate matter, and carbon dioxide on summer monsoon climate in East Asia - Danyang Ma; Tijian Wang; Beiyao Xu; Rong Song; Libo Gao; Huimin Chen; Xuejuan Ren; Shu Li; Bingliang Zhuang; Mengmeng Li; Min Xie; Eri Saikawa (Atmospheric Environment, 2023)

Overexpression of two CONSTANS-like 2 (MiCOL2) genes from mango delays flowering and enhances tolerance to abiotic stress in transgenic Arabidopsis - Rong-Zhen Liang; Cong Luo; Yuan Liu; Wan-Li Hu; Yi-Hang Guo; Hai-Xia Yu; Ting-Ting Lu; Shu-Quan Chen; Xiu-Juan Zhang; Xin-Hua He (Plant Science, 2023)

Study on the Relationship Between Diet, Physical Health and Gut Microflora of Chinese College Students - Xiafen Hu; Jiaqi Guo; Jiadun Wang; Wanxin Liu; Xiaochen Xiang; Siyang Chen; Xinquan Li; Jinhan Tang; Wei Zhang; Hui Chen; Rong Shu; Qingming Wu; et al. (Current Microbiology, 2022)

Does the institutional environment influence corporate social responsibility? Consideration of green investment of enterprises—evidence from China - Shu-Rong Han; Pei Li; Jian-Jun Xiang; Xiang-Hua Luo; Chun-Yan Chen (Environmental Science and Pollution Research, 2022)

Bioactive polyketides from the pathogenic fungus of Epicoccum sorghinum - Ching-Chia Chang; Chi-Ying Li; Yi-Hong Tsai; Mohamed El-Shazly; Chien-Kei Wei; Zih-Jie Yang; Shu-Li Chen; Chin-Chung Wu; Yang-Chang Wu; Fang-Rong Chang (Planta, 2021)

Influence of Aphis gossypii feeding on defense strategy of native and introduced populations of Ageratina adenophora - Ying Lin; Shu-Qi He; Zhi-Hui Lu; Yu-Lin Gao; Yan-Ru Duan; Zheng-Yue Li; Bin Chen; Fu-Rong Gui (Arthropod-Plant Interactions, 2020)

Construction of a single nucleotide polymorphism marker based QTL map and validation of resistance loci to bacterial wilt caused by Ralstonia solanacearum species complex in tomato - Il Sheob Shin; Jung-Ching Hsu; Shu-Mei Huang; Jaw-Rong Chen; Jaw-Fen Wang; Peter Hanson; Roland Schafleitner (Euphytica, 2020)
Bacterial wilt (BW), caused by Ralstonia solanacearum species complex is one of the major biotic factors limiting tomato production in the humid tropics. Pyramiding of resistance genes through marker-assisted selection is an efficient way to develop durable BW resistant cultivars. Tomato line ‘Hawaii 7996’ (H7996) is a stable and robust resistance source against various strains of the species complex. Major BW resistance quantitative trait loci (QTLs) Bwr - 12 and Bwr - 6 , and several minor or strain specific QTLs have been coarse-mapped in this line, but none has been fine-mapped and validated. The objective of the current study was to construct a high density genetic map using single-nucleotide polymorphism (SNP) markers derived from genotyping-by-sequencing, fine-map Bwr - 12 and Bwr - 6 and determine the effects of these QTLs using a near isogenic line (NIL) population. A high density genetic map using 1604 SNP markers with an average distance of 0.82 cM was developed for 188 F 9 recombinant inbred lines derived from the cross H7996 × WVa700. A total of seven QTLs associated with BW resistance to race 1-phylotype I ( R. pseudosolanacearum ) or/and race 3-phylotype II ( R. solanacearum ) strains were located on chromosomes 6 ( Bwr - 6.1 , 6.2 , 6.3 and 6.4 ) and 12 ( Bwr - 12.1 , Bwr - 12.2 and Bwr - 12.3 ) with logarithm of odds (LOD) scores of 6.2–15.6 and 6.2–31.1, explaining 14.2–33.4% and 15.9–53.9% of the total phenotypic variation contributed from H7996, respectively. To validate the genetic effects of the two QTL regions, a set of 80 BC 3 F 3 NILs containing different sections of Bwr -6 with or without Bwr -12 was phenotyped for disease severity after challenge with either race 1-phylotype I Pss4 or race 3-phylotype II Pss1632 BW strains over two seasons. Bwr -6.1 specific to Pss4 and Bwr -6.3 specific to Pss1632 were mapped to an interval of 5.0 cM ( P < 0.05) between 6_33,444,000_SLM6-47 and 6_33,868,000_SLM6-124 SNP marker, and to 2.7 cM ( P < 0.01) between positions 6_35,949,000 _SLM6-107 to 6_36,750,000_SLM6-82 marker, respectively. In addition, the specific effect of Bwr -12 for resistance to Pss4 (LOD score of 5.8-16.1, P < 0.01) was confirmed.

Sol-gel hydrothermal synthesis of nano crystalline silicotitanate and its strontium and cesium adsorption - Rong Wang; Zhenggang Luo; Qiuxia Tan; Rui Wang; Shuyuan Chen; Jiancheng Shu; Mengjun Chen; Zhengxue Xiao (Environmental Science and Pollution Research, 2020)

Photoperiod-dependent release of suppression pheromone in the male lobster cockroach Nauphoeta cinerea - Rong Kou; Shu-Chun Chen; Rou-Ling Yang; Chu-Chun Hsu (The Science of Nature, 2019)

Paramyxoviruses respiratory syncytial virus, parainfluenza virus, and human metapneumovirus infection in pediatric hospitalized patients and climate correlation in a subtropical region of southern China: a 7-year survey - Wen-Kuan Liu; De-Hui Chen; Wei-Ping Tan; Shu-Yan Qiu; Duo Xu; Li Zhang; Shu-Jun Gu; Rong Zhou; Qian Liu (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

The complete chloroplast genome of the daimyo oak, Quercus dentata Thunb. - Hua-Lei Hu; Jing-Yu Zhang; Yu-Ping Li; Lu Xie; Dong-Bin Chen; Qun Li; Yan-Qun Liu; Shu-Rong Hui; Li Qin (Conservation Genetics Resources, 2019)

Candida glabrata-Induced Refractory Infectious Arthritis: A Case Report and Literature Review - Shu Chen; Yi Chen; Yi-qin Zhou; Ning Liu; Rong Zhou; Jin-hui Peng; Qi-rong Qian (Mycopathologia, 2019)

Endogenous Hydrogen Sulfide Promotes Apoptosis via Mitochondrial Pathways in the Livers of Broilers with Selenium Deficiency Exudative Diathesis Disease - Shu-fang Zheng; Rong-kun Bao; Qiao-jian Zhang; Sheng-chen Wang; Hong-jin Lin (Biological Trace Element Research, 2018)

Unexpected dose response of HaCaT to UVB irradiation - Rong-Shing Chang; Chi-Shuo Chen; Ching-Lung Huang; Chiu-Ting Chang; Yujia Cui; Wei-Ju Chung; Wun-Yi Shu; Chi-Shiun Chiang; Chun-Yu Chuang; Ian C. Hsu (In Vitro Cellular & Developmental Biology - Animal, 2018)

Epidemiology and clinical characteristics of human coronaviruses OC43, 229E, NL63, and HKU1: a study of hospitalized children with acute respiratory tract infection in Guangzhou, China - Zhi-Qi Zeng; De-Hui Chen; Wei-Ping Tan; Shu-Yan Qiu; Duo Xu; Huan-Xi Liang; Mei-Xin Chen; Xiao Li; Zheng-Shi Lin; Wen-Kuan Liu; Rong Zhou (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

EGFL7-overexpressing epidermal stem cells promotes fibroblast proliferation and migration via mediating cell adhesion and strengthening cytoskeleton - Rong-Hua Yang; Shao-Hai Qi; Shu-Bin Ruan; Ze-Peng Lin; Yan Lin; Feng-Gang Zhang; Xiao-Dong Chen; Ju-Lin Xie (Molecular and Cellular Biochemistry, 2016)

The miR-573/apoM/Bcl2A1-dependent signal transduction pathway is essential for hepatocyte apoptosis and hepatocarcinogenesis - Yan-Wei Hu; Zhi-Ping Chen; Xiu-Mei Hu; Jia-Yi Zhao; Jin-Lan Huang; Xin Ma; Shu-Fen Li; Yu-Rong Qiu; Xiao-Juan Wu; Yan-Hua Sha; Ji-Juan Gao; Yan-Chao Wang; et al. (Apoptosis, 2015)

Modified method for estimating organic carbon density in discontinuous Karst soil using ground-penetrating radar and geostatistics - Lei Li; Yin-hang Xia; Shu-juan Liu; Wei Zhang; Xiang-bi Chen; Hua Zheng; Hu-sen Qiu; Xun-yang He; Yi-rong Su (Journal of Mountain Science, 2015)

Partitioning of Aromatic Constituents into Water from Jet Fuels - Chien-Jung Tien; Youn-Yuen Shu; Shih-Rong Ciou; Colin S. Chen (Archives of Environmental Contamination and Toxicology, 2015)

Isolation and characterisation of Bacillus spp. antagonistic to Vibrio parahaemolyticus for use as probiotics in aquaculture - Xue-Fei Liu; Ya Li; Jian-Rong Li; Lu-Yun Cai; Xiu-Xia Li; Jin-Ru Chen; Shu-Xia Lyu (World Journal of Microbiology and Biotechnology, 2015)

The Marginal Division of the Striatum and Hippocampus Has Different Role and Mechanism in Learning and Memory - Si-Yun Shu; Gang Jiang; Qi-Yi Zeng; Bin Wang; Hong Li; Lin Ma; Harry Steinbusch; Cai Song; Wood-Yee Chan; Xu-Hong Chen; Yon-Ming Wu; Rong Bao; et al. (Molecular Neurobiology, 2015)

Abundance and distribution of fatty acids in sediments of the South Mid-Atlantic Ridge - Xin Huang; Zhigang Zeng; Shuai Chen; Xuebo Yin; Xiaoyuan Wang; Yao Ma; Baoju Yang; Kunbo Rong; Yunchao Shu; Tao Jiang (Journal of Ocean University of China, 2015)

Component characteristics of polycyclic aromatic compounds in sediments of the South Mid-Atlantic Ridge - Xin Huang; Zhigang Zeng; Shuai Chen; Xuebo Yin; Xiaoyuan Wang; Yao Ma; Baoju Yang; Kunbo Rong; Yunchao Shu; Tao Jiang (Acta Oceanologica Sinica, 2014)

Clodronate-superparamagnetic iron oxide-containing liposomes attenuate renal injury in rats with severe acute pancreatitis - Sheng-chun Dang; Yan-hua Zeng; Ping-jiang Wang; Bao-ding Chen; Rong-fang Chen; Arun Kumar Singh; Pankaj Kumar; Shu Feng; Lei Cui; Hao Wang; Jian-xin Zhang (Journal of Zhejiang University-SCIENCE B, 2014)

Comparative genomics of the marine bacterial genus G laciecola reveals the high degree of genomic diversity and genomic characteristic for cold adaptation - Qi‐Long Qin; Bin‐Bin Xie; Yong Yu; Yan‐Li Shu; Jin‐Cheng Rong; Yan‐Jiao Zhang; Dian‐Li Zhao; Xiu‐Lan Chen; Xi‐Ying Zhang; Bo Chen; Bai‐Cheng Zhou; Yu‐Zhong Zhang (Environmental Microbiology, 2014)
Summary To what extent the genomes of different species belonging to one genus can be diverse and the relationship between genomic differentiation and environmental factor remain unclear for oceanic bacteria. With many new bacterial genera and species being isolated from marine environments, this question warrants attention. In this study, we sequenced all the type strains of the published species of G laciecola , a recently defined cold‐adapted genus with species from diverse marine locations, to study the genomic diversity and cold‐adaptation strategy in this genus. The genome size diverged widely from 3.08 to 5.96 M b, which can be explained by massive gene gain and loss events. Horizontal gene transfer and new gene emergence contributed substantially to the genome size expansion. The genus G laciecola had an open pan‐genome. Comparative genomic research indicated that species of the genus G laciecola had high diversity in genome size, gene content and genetic relatedness. This may be prevalent in marine bacterial genera considering the dynamic and complex environments of the ocean. Species of G laciecola had some common genomic features related to cold adaptation, which enable them to thrive and play a role in biogeochemical cycle in the cold marine environments.

Association between melatonin receptor 1A (MTNR1A) gene single-nucleotide polymorphisms and the velvet antler yield of Sika deer - Fei-Fei Yang; Li-Jun Huo; Li-Guo Yang; Hasan Riaz; Li-Rong Xiong; Jian-Guo Chen; Shu-Jun Zhang; Jia-Jun Xiong (Molecular Biology Reports, 2014)

Charlson comorbidity index helps predict the risk of mortality for patients with type 2 diabetic nephropathy - You-Qun Huang; Rong Gou; Yong-Shu Diao; Qing-Hua Yin; Wen-Xing Fan; Ya-Ping Liang; Yi Chen; Min Wu; Li Zang; Ling Li; Jing Zang; Lu Cheng; et al. (Journal of Zhejiang University-SCIENCE B, 2014)

Influence of ORM1 polymorphisms on the maintenance stable warfarin dosage - Lian Sheng Wang; Jing Jing Shang; Shu Ya Shi; Yan Qing Zhang; Jian Lin; Zhi Hua Guo; Yi Chen Wang; Jie Tang; Jie Liu; Ying Zi Liu; Zhi Li; Zhi Rong Tan; et al. (European Journal of Clinical Pharmacology, 2013)

Halomonas qijiaojingensis sp. nov. and Halomonas flava sp. nov., two moderately halophilic bacteria isolated from a salt lake - Chao Chen; Rong Shi; Bing-Bing Liu; Yun-Jiao Zhang; Hong-Zhuan Sun; Chang-Tian Li; Shu-Kun Tang; Li-Li Zhang; Wen-Jun Li (Antonie van Leeuwenhoek, 2011)

Increased urinary 8-hydroxy-2′-deoxyguanosine levels in workers exposed to di-(2-ethylhexyl) phthalate in a waste plastic recycling site in China - Qian Wang; Li Wang; Xi Chen; Kai Min Rao; Shao You Lu; Sheng Tao Ma; Pu Jiang; Dan Zheng; Shun Qing Xu; Hong Yan Zheng; Jian Shu Wang; Zhi Qiang Yu; et al. (Environmental Science and Pollution Research, 2011)

Comparison of DNA extraction methods for the PCR-single-strand-conformation polymorphism analysis of kefir - Shu-Jun Chen; Qing Wang; Jian-Rong Han; Yu Wang; Zhi-Wei Li (World Journal of Microbiology and Biotechnology, 2011)

Detection of survivin-expressing circulating cancer cells in the peripheral blood of patients with esophageal squamous cell carcinoma and its clinical significance - Mei Cao; Shang-Mian Yie; Sheng-Min Wu; Shu Chen; Be Lou; Xu He; Shang-Rong Ye; Ke Xie; Lin Rao; En Gao; Nai-Yao Ye (Clinical & Experimental Metastasis, 2009)

Phase I clinical trial on intracoronary administration of Ad-hHGF treating severe coronary artery disease - Zhi-Jian Yang; You-Rong Zhang; Bo Chen; Shu-Lan Zhang; En-Zhi Jia; Lian-Sheng Wang; Tie-Bing Zhu; Chun-Jian Li; Hui Wang; Jun Huang; Ke-Jiang Cao; Wen-Zhu Ma; et al. (Molecular Biology Reports, 2009)

Suppression pheromone and cockroach rank formation - Rong Kou; Huan-Wen Chang; Shu-Chun Chen; Hsiao-Yung Ho (The Science of Nature, 2009)

Molecular cloning, characterization and expression of atpA and atpB genes from Ginkgo biloba - Feng Xu; Rong Cai; Shui-yuan Cheng; Liu-ji Chen; Shu-han Cheng (Biologia, 2008)

A new dibenzofuran and other constituents from Ligularia caloxantha , a chinese medicinal plant - Shu-Yun Shi; Ming-Hui Hu; Di-Yao Wu; Chang-Xin Zhou; Jian-Xia Mo; Juan-Hua Xu; Liu-Rong Chen; Hui Dou; Hua Peng; Xiao-Jiang Hao; Joachim Stöckigt; Yu Zhao (Natural Product Research, 2008)

Strategic 3-hydroxy-2-butanone release in the dominant male lobster cockroach, Nauphoeta cinerea - Shu-Chun Chen; Rou-Ling Yang; Hsiao-Yung Ho; Szu-Ying Chou; Rong Kou (The Science of Nature, 2007)

Proteomic profiling of proteins dysregulted in Chinese esophageal squamous cell carcinoma - Xiao-Li Du; Hai Hu; De-Chen Lin; Shu-Hua Xia; Xiao-Ming Shen; Yu Zhang; Man-Li Luo; Yan-Bin Feng; Yan Cai; Xin Xu; Ya-Ling Han; Qi-Min Zhan; et al. (Journal of Molecular Medicine, 2007)

Characterization of a novel T4-type Stenotrophomonas maltophilia virulent phage Smp14 - Chiy-Rong Chen; Ching-Hsuan Lin; Juey-Wen Lin; Chi-I Chang; Yi-Hsiung Tseng; Shu-Fen Weng (Archives of Microbiology, 2007)

3-Hydroxy-2-butanone and the first encounter fight in the male lobster cockroach, Nauphoeta cinerea - Rong Kou; Shu-Chun Chen; Ying-Ru Chen; Hsiao-Yung Ho (The Science of Nature, 2006)

Cloning, expression and genomic structure of a novel human GNB2L1 gene, which encodes a receptor of activated protein kinase C (RACK)* - Shu Wang; Jin-zhong Chen; Zhen Zhang; Shaohua Gu; Chaoneng Ji; Rong Tang; Kang Ying; Yi Xie; Yumin Mao (Molecular Biology Reports, 2003)

Cloning and identification of a cDNA that encodes a novel human protein with thrombospondin type I repeat domain, hPWTSR - Jin-Zhong Chen; Shu Wang; Rong Tang; Quan-Sheng Yang; Enpeng Zhao; Yaoqiong Chao; Kang Ying; Yi Xie; Yu-Min Mao (Molecular Biology Reports, 2002)

The role of CYP2C19 in amitriptyline N-demethylation in Chinese subjects - Zhi-Ping Jiang; Yan Shu; Xiao-Ping Chen; Song-Lin Huang; Rong-Hua Zhu; Wei Wang; Nan He; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2002)

Symposia lectures - F. Parak; A. Ostermann; G. U. Nienhaus; Nobuo Niimura; William A. Eaton; Stephen J. Hagen; Eric R. Henry; James Hofrichter; Gouri Jas; Lisa Lapidus; Victor Muñoz; Chih-chen Wang; et al. (Journal of Biosciences, 1999)